I did not feel like a mother: the success and remaining challenges to exclusive formula feeding among HIV-positive women in Brazil - MacCarthy, Sarah (2014)
Exclusive and safe formula feeding can eliminate the risk of vertical HIV transmission due to breastfeeding. Therefore many countries advise all HIV-positive women to avoid breastfeeding their infants. However, little research explores the experiences of women attempting to exclusively formula feed (EFF) in countries with free and universal access to HAART. This article examines the success of Brazil in supporting HIV-positive women as they EFF their infants. We conducted in-depth interviews with 30 HIV-positive women receiving care at the primary facility for HIV/AIDS in Salvador, Brazil about their attitudes and practices related to EFF as well as challenges with adhering to EFF. All interviews were recorded, professionally transcribed and translated, and then analyzed. Our results showed that one woman reported both breastfeeding and formula feeding her infant; all others reported EFF. Postpartum counseling regarding the risk of HIV transmission through breastfeeding was the primary motivation for EFF. Challenges included difficulty reconciling their perceptions that breastfeeding is an important maternal responsibility, trouble accepting that breastfeeding can cause potential to harm their infants, confronting HIV-related stigma associated with EFF, and unexpected financial burdens due to EFF. We conclude that HIV-positive women adhered to national guidelines recommending EFF; this phenomenon has likely contributed to declining rates of vertical transmission in Brazil. Despite this success, many women experienced challenges with EFF. Greater support services may enhance Brazil’s success in empowering HIV-positive women and eliminating vertical HIV transmission via breastfeeding.